The effect of Contextual Teaching Learning (CTL) and Teams Games Tournaments (TGT) learning methods on physical fitness satisfaction levels - Asep Ruhiat; Dewi Susilawati; Yudha M Saputra (STKIP Muhammadiyah Kuningan, 2023)
This experimental research was implemented in two elementary schools, namely SDN Kaduronyo 1 as the experimental class and SDN Palembang 2 as the control class. Before carrying out the research, the conditions must be met: the population and sample must be homogeneous or the same. When the two groups are homogeneous or the same, then normality can be measured by carrying out the normality test. The normality test results showed that the initial questionnaire data for experimental learning outcomes was 0.094> 0.05, the final questionnaire for experimental learning outcomes was 0.088> 5, the significance of the experimental group pretest was 0.034> 0.05, and the post-test experiment was 0.19. Meanwhile, from the results of the normality test for the control class, it was found that the initial questionnaire data for control learning outcomes was 0.200> 0.05, the initial questionnaire for control learning outcomes was 0.200> 0.05, the post-test for the control group 0.200> 0.05 and post-test 0.200> 0.05. So the data from the experimental group are normally distributed. So, the data from the control group are normally distributed. The results of the Contextual Teaching and Learning (CTL) and Teams Games Tournaments (TGT) learning methods on high Physical Fitness can be seen from the calculation of increased student learning outcomes, from 13.3% to 17.8%. There is a significant influence of the Contextual Teaching and Learning (CTL) and Teams Games Tournaments (TGT) learning methods on Physical Fitness; this can be seen from the results of the independent sample t-test calculation on learning outcomes it can be seen that the price is sig = 0.001 with a significance level of 0.05. Thus the probability is smaller than 0.05. This fact shows that the variance of learning outcomes between the experimental and control classes has a significant effect.